Análise exergética e ecológica de um sistema compacto de cogeração operando com gás de síntese - Kawabe Junior, Eduardo Massashi [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The aim of this work is to make a qualitatively and ecologically evaluation of a compact cogeneration system that operates with synthesis gas obtained from a gasifier. Using the Eucalyptus Biomass as fuel, that passes through a wood gasifier (Drowndraft type) and supply the internal combustion engine. The compact cogeneration system is composed of two heat exchangers, an energy generator connected to an internal combustion engine and an absorption refrigeration system. The complete system is installed in the laboratory from the Energy Department at the University of Guaratinguetá. By the analysis related to the First and Second Thermodynamic Laws applied in this system, was possible to identify the mass flows in each point, energetic efficiency, irreversibility and exergetic efficiency. The components that have the biggest irreversibilities are the gasifier, followed by the internal combustion engine, which should be focused in future improvements. The system efficiency in energetic basis is 51,84% and in exergetic basis is 22,78%. Using the ecologic efficiency methodology was possible to identify the emissions rates, the pollution indicator associated to the combustion of the synthesis gas in the internal combustion engine. The ecologic efficiency considering the energectic analysis is 91,73%, while considering the exergetic analysis, 83,65%. It is concluded that the use of the synthesis gas in a compact cogeneration system is viable from the technical and ecological point of view, making possible to generate energy for isolated communities and promoting the decentralized electricity generation

O objetivo desse trabalho é avaliar de maneira qualitativa e ecológica um sistema compacto de cogeração operando com gás de síntese proveniente de um gaseificador. Utiliza-se a biomassa de eucalipto como combustível que passa por um gaseificador de madeira do tipo Drowndraft e alimenta o motor de combustão interna. O sistema compacto de cogeração é composto por dois trocadores de calor, um gerador acoplado a um motor de combustão interna e um sistema de refrigeração por absorção. O sistema completo deste estudo encontra-se instalado no Laboratório do Departamento de Energia da Faculdade de Guaratinguetá. Através de análises relacionadas a Primeira e Segunda Leis da Termodinâmica aplicadas neste sistema foi possível identificar vazões mássicas de cada fluxo, rendimento energético, irreversibilidade e rendimento exergético. Os componentes que possuem maiores irreversibilidades são o gaseificador, seguido do motor de combustão interna, que devem ser foco para futuras melhorias. A eficiência do sistema em base energética é de 51,84% e em base exergética de 22,78%. Através do uso da metodologia de eficiência ecológica foi possível identificar os índices de emissões, o indicador de poluição associado a combustão do gás de síntese no motor de combustão interna. A eficiência ecológica considerando a análise em base energética é de 91,73% e em base exergética 83,65%. Conclui-se que o uso de gás síntese em sistema de cogeração compacta é viável sob o ponto de vista técnico e ecológico, possibilitando gerar energia para comunidades isoladas e favorecendo a geração descentralizada
Keywords: Biomassa; Energia eletrica e calor - Cogeração; Motores de combustão interna; Gases de combustão; Biomass; Internal combustion engine; Cogeneration